[Rezension von: Drimbe, Amiel, 1980-, The church of Antioch and the eucharistic traditions (ca. 35-130 CE)] - Stewart-Sykes, Alistair; Drimbe, Amiel 1980- (2021)
For reasons which will become apparent I will state a conclusion at the outset: this is a well-researched, mostly well-argued, extremely well-written, and invariably interesting monograph.Its purpose is to trace developments within the Antiochene church (the singular here is deliberate) from the time of the breach between Peter and Paul reported in Galatians to the time of Ignatius (who, the author suggests, is a Trajanic or perhaps Hadrianic figure). The lens through which these developments are sought is the eucharistic practice of this church. Thus the author studies the Pauline report of the last supper addressed to the Corinthians, the last supper narrative of Matthew, the Didachistic eucharist of chapters 9 and 10, and the eucharistic practice of Ignatius. All of these are taken to reflect the liturgical conditions of Antioch. In summary, Drimbe sees these various usages giving way to each other, and in some cases running concurrently, but not actually as ever competing. This, the author suggests, is an example of interactive diversity within a single Antiochene church.
Keywords: Rezension